Fuzzy system dynamics risk analysis (FuSDRA) of autonomous underwater vehicle operations in the Antarctic - Loh, TY; Brito, MP; Neil Bose; Xu, Jingjing; Kiril Tenekedjiev (2019)
With the maturing of autonomous technology and better accessibility, there has been a growing interest in the use of Autonomous Underwater Vehicles (AUVs). The deployment of AUVs for under-ice marine science research in the Antarctic is one such example. However, a higher risk of AUV loss is present during such endeavours due to the extreme operating environment. Existing risk analyses approaches tend to focus more on the AUV's technical aspects but this paper shows that organisational, human and external influences also play a significant role in influencing the risk of AUV loss. The dynamic and complex inter-relationships of risk variables are also often overlooked due to ambiguity and vagueness. To overcome these shortfalls, an integrated fuzzy system dynamics risk analysis (FuSDRA) is proposed. In FuSDRA, system dynamics models the dynamic inter-relationships between risk variables from different dimensions while fuzzy logic accounts for vagueness and ambiguity. An application example based on the nupiri muka AUV program is presented. The combined effect of funding and experience of the AUV team showed a declining risk of loss from 0.293 in the early years of the AUV program, reaching a minimal of 0.206 before increasing again in later years. Risk control policy recommendations were then explored through changing the initial average experience of the team, and varying external commercial and internal research demand. The example clearly demonstrated how FuSDRA can be applied to inform funding and risk management strategies, or broader application both within the AUV domain and on other science complex technological systems